Microtubule‐Binding Proteins as Promising Biomarkers of Paclitaxel Sensitivity in Cancer Chemotherapy. Issue 2 (1st September 2015) - Xie, Songbo; Ogden, Angela; Aneja, Ritu; Zhou, Jun
Abstract: Microtubules, tirelessly animated and highly dynamic structures, are vital for most cellular processes and their intricacies are still being revealed even after a century since their discovery. The importance of microtubules as chemotherapeutic targets cannot be overstated, and their clinical role is unlikely to abate in the near future. Indeed, improved understanding of microtubule biology could herald a new epoch of anticancer drug design by permitting fine‐tuning of microtubule‐targeting agents, the clinical utility of which is presently often limited by primary or acquired resistance. Paclitaxel, one such agent belonging to the taxane family, has proven a resoundingly successful treatment for many cancer patients; however, for too many others with paclitaxel‐refractory tumors, the drug has offered nothing but side effects. Accumulating evidence suggests that microtubule‐binding proteins (MBPs) can regulate paclitaxel sensitivity in a wide range of cancer types. Improved understanding of how these proteins can be assayed to predict treatment responses or manipulated pharmacologically to improve clinical outcomes could transform modern chemotherapy and is urgently awaited.